P5-S7.12 STD testing in emergency department: a novel method to provide test results. (10th July 2011) - Arno, J; Messina, F; Perkins, A; Allen, A
Abstract : Background: Realising the potential of broad based STD testing depends on treatment of those with positive results. Because emergency department (ED) physicians expressed reluctance to test for STD's because they had no mechanism for giving test results, we devised a system to provide results to patients tested for STD's at the county's public hospital by calling Bell Flower, the health department's STD program, to determine whether patients tested for STD's in the ED would call for their results. Methods: An electronically generated individually modified referral note with instructions for calling Bell Flower for STD test results was given to all patients tested for STD's including gonorrhoea (GC), Chlamydia (CT) or syphilis, in the Wishard Hospital Emergency Department. The Bell Flower results clerk was given access to the hospital's electronic medical record system containing laboratory results. The clerk's access to a specific patient's results was recorded electronically by the system. Patient records accessed by the clerk were extracted and matched to patients given the discharge note. A patient was judged to have called if the clerk accessed that patient's test results. Continuous variables were compared using student t tests and proportions compared using χ 2 analysis. Because Hispanic patients used a different call mechanism, their data were excluded. Results: From 1 January 2010 to 30 April 2010, 503 patients were given the STD referral note. Of these, 447 were >14 years old, not Hispanic and had complete medical record information. Of the 447 patients with analysable data, 146 (32.7%) called for test results. Age, race, sex, Chlamydia results or treatment and high risk zip codes were unrelated to whether or not a patient called for results. Of 65 patients infected with CT 33 (52.3%) were not treated in the ED of which 10 called. Of 45 patients with GC, 6 (13.3%) were not treated for it in the ED, of which 2 called. Patients infected with GC, were less likely to call for their results than those not infected (p=0.019), particularly those who were adequately treated in the ED (p=0.039). Conclusions: Roughly one third of patients in one public hospital ED instructed to call for STD results called for them. Most of those infected with GC but not CT were treated appropriately with empiric antibiotics while in the ED. Infected patients calling in for test results could facilitate prompt treatment.